The Effect of Transformational Leadership on Employee Performance: The Mediating Roles of Work Discipline and Work Motivation at BKPSDM Ternate City - Hidayat, Taufik; Marwan, Marwan; Alhadar, Fadhliah M. (International Journal of Business, Law, and Education, 2026)
Purpose: This study examines the direct effect of transformational leadership on employee performance and the indirect effects mediated by work discipline and work motivation at the Personnel and Human Resources Development Agency (BKPSDM) of Ternate City. Design/methodology/approach: The study applied a quantitative explanatory design. The population comprised 83 employees, and 67 valid responses were analyzed. Data were collected using a five-point Likert-scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The measurement model was assessed through indicator loadings, Average Variance Extracted (AVE), cross-loadings, the Fornell-Larcker criterion, HTMT, Cronbach's alpha, and composite reliability. The structural model was evaluated using R-square, f-square, Q-square, path coefficients, and bootstrapping with 5,000 subsamples. Findings: Transformational leadership significantly improves employee performance, work discipline, and work motivation. Work discipline significantly improves employee performance and mediates the relationship between transformational leadership and employee performance. In contrast, work motivation does not significantly affect employee performance and does not mediate the relationship. Originality/value: The findings clarify that, in a regulation-based public-sector setting, leadership contributes to employee performance more strongly through disciplined work behavior than through motivational mechanisms alone.